(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
In modern society, innovation technologies expand to almost every field of human activity, including such wide field as education. Due to integrating innovation technologies into the educational process practice, this phenomenon gained special significance within improvement and modernization of the established educational system. Currently, the problem of active integration and wide application of innovation technologies in education is highly significant. Present study explores innovation technologies of learning in the modern education